1993
DOI: 10.1073/pnas.90.18.8595
|View full text |Cite
|
Sign up to set email alerts
|

Giardiavirus double-stranded RNA genome encodes a capsid polypeptide and a gag-pol-like fusion protein by a translation frameshift.

Abstract: Giardiavirus is a small, nonenveloped virus comprising a monopartite double-stranded RNA genome, a major protein of 100 kDa, and a less abundant polypeptide of 190 kDa. It can be Isolated from the culture supernatant of Giardia lwnblia, a parasitic flagellate in human and other mammals, and effclently infects other virus-free G. lamblia. A single-stranded copy of the viral RNA can be electroporated into uninfected G. amblia cells to complete the viral replication cyde. Giardiavirus genomic cDNA of 6100 nt was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 35 publications
(19 reference statements)
2
81
0
Order By: Relevance
“…Giardiavirus (GLV) is a double-stranded (ds)RNA virus of the Totiviridiae family, which specifically infects trophozoites of the most primitive protozoan parasite Giardia lambila (Wang & Wang, 1986)+ Its dsRNA genome of 6277 bp encodes two polypeptides; a major 100-kDa capsid protein (Gag) and a minor 190-kDa fusion protein (Gag-Pol) via a Ϫ1 ribosomal frameshift (Wang et al+, 1993;Li et al+, 2001)+ The coding region in GLV (ϩ)-strand RNA is flanked by a 367-nt 59 untranslated region (UTR) and a 301-nt 39 UTR + The ability of purified GLV to infect, and the capability of its (ϩ)-stranded RNA to transfect G. lamblia trophozoites, resulting in intracellular proliferation of infectious GLV particles, are the major distinguishing features of this virus among the totiviruses (Wang & Wang, 1986)+ It has turned the GLV (ϩ)-strand RNA into an effective transfection vector for high-level expression of foreign mRNAs in GLVinfected G. lamblia (Yu et al+, 1995;Yu & Wang, 1996)+ In vitro-transcribed chimeric mRNA containing a fulllength firefly luciferase transcript flanked by the 367-nt GLV 59 UTR and a 2022-nt 39 terminus of GLV (ϩ)-strand RNA can be introduced into GLV-infected G. lamblia trophozoites via electroporation (Yu et al+, 1995)+ The chimeric mRNA thus introduced undergoes vigorous replication and transcription but only a basal level of translation, resulting in an expressed luciferase activity barely above the background level (Yu et al+, 1995;Yu & Wang, 1996)+ This relatively poor translation efficiency was, however, enhanced by 5,000-fold when the initial 264 nt of the capsid-coding region in GLV mRNA were fused in frame with, and upstream from, the luciferase mRNA (Yu & Wang, 1996)+ In our earlier studies, we have identified a 13-nt downstream box (DB) sequence within the initial 264-nt capsid coding region of GLV mRNA at position 66-78 that complements a 15-nt sequence (with two gaps) between nt 1382 and 1396 in the V9 region near the 39 end of the 16S-like ribosomal RNA (rRNA) of G. lamblia (Yu et al+, 1998)+ Deletion or scrambling of this DB sequence led to a significant loss of translation efficiency+ However, although DB is located 66-78 nt downstream of the start codon, inclusion of the first 98 nt of the downstream region encompassing the entire DB exerted little enhancement of translation of the chimeric transcript (Yu & Wang, 1996)+ It was the increment of coding region from nt 111 to 264 that resulted in an exponential increase of translation efficiency up to 5,000-fold (Yu & Wang, 1996)+ The entire 264-nt segment of GLV mRNA has since been thoroughly analyzed for additional structural and sequence-specific elements that may contribute to the enhanced translation+ Results from chemical probing and mutational analysis of the MFOLD-predicted stemloops I (nt 11-35), verified their presence in the RNA molecule and indicated their essential involvement in enhanced translation (Garlapati et al+, 2001)+ Similar experiments also demonstrated the presence and ...…”
Section: Introductionmentioning
confidence: 99%
“…Giardiavirus (GLV) is a double-stranded (ds)RNA virus of the Totiviridiae family, which specifically infects trophozoites of the most primitive protozoan parasite Giardia lambila (Wang & Wang, 1986)+ Its dsRNA genome of 6277 bp encodes two polypeptides; a major 100-kDa capsid protein (Gag) and a minor 190-kDa fusion protein (Gag-Pol) via a Ϫ1 ribosomal frameshift (Wang et al+, 1993;Li et al+, 2001)+ The coding region in GLV (ϩ)-strand RNA is flanked by a 367-nt 59 untranslated region (UTR) and a 301-nt 39 UTR + The ability of purified GLV to infect, and the capability of its (ϩ)-stranded RNA to transfect G. lamblia trophozoites, resulting in intracellular proliferation of infectious GLV particles, are the major distinguishing features of this virus among the totiviruses (Wang & Wang, 1986)+ It has turned the GLV (ϩ)-strand RNA into an effective transfection vector for high-level expression of foreign mRNAs in GLVinfected G. lamblia (Yu et al+, 1995;Yu & Wang, 1996)+ In vitro-transcribed chimeric mRNA containing a fulllength firefly luciferase transcript flanked by the 367-nt GLV 59 UTR and a 2022-nt 39 terminus of GLV (ϩ)-strand RNA can be introduced into GLV-infected G. lamblia trophozoites via electroporation (Yu et al+, 1995)+ The chimeric mRNA thus introduced undergoes vigorous replication and transcription but only a basal level of translation, resulting in an expressed luciferase activity barely above the background level (Yu et al+, 1995;Yu & Wang, 1996)+ This relatively poor translation efficiency was, however, enhanced by 5,000-fold when the initial 264 nt of the capsid-coding region in GLV mRNA were fused in frame with, and upstream from, the luciferase mRNA (Yu & Wang, 1996)+ In our earlier studies, we have identified a 13-nt downstream box (DB) sequence within the initial 264-nt capsid coding region of GLV mRNA at position 66-78 that complements a 15-nt sequence (with two gaps) between nt 1382 and 1396 in the V9 region near the 39 end of the 16S-like ribosomal RNA (rRNA) of G. lamblia (Yu et al+, 1998)+ Deletion or scrambling of this DB sequence led to a significant loss of translation efficiency+ However, although DB is located 66-78 nt downstream of the start codon, inclusion of the first 98 nt of the downstream region encompassing the entire DB exerted little enhancement of translation of the chimeric transcript (Yu & Wang, 1996)+ It was the increment of coding region from nt 111 to 264 that resulted in an exponential increase of translation efficiency up to 5,000-fold (Yu & Wang, 1996)+ The entire 264-nt segment of GLV mRNA has since been thoroughly analyzed for additional structural and sequence-specific elements that may contribute to the enhanced translation+ Results from chemical probing and mutational analysis of the MFOLD-predicted stemloops I (nt 11-35), verified their presence in the RNA molecule and indicated their essential involvement in enhanced translation (Garlapati et al+, 2001)+ Similar experiments also demonstrated the presence and ...…”
Section: Introductionmentioning
confidence: 99%
“…The genomic organization and genetic diversity of TVV resemble the non-segmented dsRNA viruses of the Totiviridae family, including the Saccharomyces cerevisiae virus (ScV), Giardia lamblia virus (GLV) and Leishmania RNA virus (LRV) (Icho and Wickner, 1989;Bruenn, 1993;Wang et al, 1993;Stuart et al, 1992;Scheffter et al, 1994Scheffter et al, , 1995. The RdRps of ScV L-A, ScV L-BC, GLV, LRV 1-1, 1-4 and 2-1 were included in order to analyze the intergeneric relationship of these viruses in the Totiviridae family (GenBank Accession no.…”
Section: Phylogenic Analysismentioning
confidence: 99%
“…The capsids consists of single major capsid proteins and minor RDRPs. Several studies Wang et al, 1993) suggest that both organization and replication strategies of protozoan viruses are similar to those of yeast, whose genome contains an upstream cap gene and a downstream pol gene in the (þ)-strand RNA. The cap gene encodes a capsid protein and pol encodes an RDRP that is synthesized from the initiation of the capsid protein via a ribosomal frameshift mechanism.…”
Section: Introductionmentioning
confidence: 99%